(3GdedbHGJ GdaQVjIs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3bGd GdabjQ YeQ Hf GdhQOi hgPg GdQSGj GdgPHI VefJgG GdeSGjd GdedbHI GdChdi GdeTQcI s
(3BNQgG (B:s
(3hHjf GYOGO GdQDS JSei dGLd eG PcQJg HUeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B553s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGFV GdePGgH (B22 (3e(B) s
Keywords: (3Yde GdaQGFVs